Charismatic Leadership and Participation Strengthening Innovation Culture in HRM Planning - Paroli, Paroli; Evans, Richard (Aptisi Transactions On Technopreneurship (ATT), 2026)
Innovative Human Resource Management (HRM) planning is necessary for public sector organisations amidst digital transformation and bureaucratic decentralisation demands. However, efforts to form a culture of innovation in HRM planning often face structural, cultural, and participatory obstacles. This study aims to analyse the influence of charismatic leadership, the culture of innovation, and employee participation on forming a culture of innovation in HRM planning and evaluate the moderating role of employee participation in the relationship. This study uses a quantitative approach with an explanatory type conducted on local government employees in 27 districts/cities in West Java Province, Indonesia. A sample of 200 respondents was selected by purposive sampling, namely civil servants directly involved in planning and implementing HR policies. Data collection techniques were carried out through distributing questionnaires, while data analysis used the Partial Least Squares - Structural Equation Modeling (PLS-SEM) method. The results showed that charismatic leadership, innovation culture, and employee participation significantly influence the formation of innovation culture in HRM planning. In addition, employee participation is shown to moderate the effect of charismatic leadership positively but negatively moderate the relationship between innovation culture and the formation of innovation culture. These findings suggest that participation management needs to be strategically designed to avoid the burden of counterproductive roles. These results confirm the importance of strengthening leadership capacity, instilling organisational innovation values, and effective participation management in building an HRM planning system that is adaptive, collaborative, and aligned with the spirit of startup-era governance.